Help-seeking behaviour of adolescents in a Singapore secondary school - Foong, Yin Wei. (2008)
The help-seeking behaviour of 325 adolescents in a Singapore school was examined as a function of students' personal characteristics and their perceptions of their environment, and their tendencies to use different help-seeking strategies for academic problems. Self-report questionnaires were used.